Mythonymy in English Folk Tale - Anvarovna, Turdiyeva Nilufar; Anvarovna , Djabborova Nigina (Research Parks Publishing LLC, 2022)
The article discusses some features of the use of mythonyms in English fairy tales, taking into account the etymology, are discussed in the article.